Fecundity and maturation of gonad of snakehead fish Channa striatus (Block, 1793) (Channiformes : Channidae) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Channa striatus, fecundity, gonad Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 65-67